Implication of endocrine disruption in selected reef fishes to fish ecology in Iligan City - Nuñeza, Olga M. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2007)
Iligan City the industrial city of the south is home to processing industries believed to be sources of effluents that may contain endocrine disrupting compounds (EDCs). The city is also a fishing community with a number of commercial and non-commercial fish species. These industries and fishing grounds are within the localities of six coastal villages of Iligan City where our samples came from during the June to July sampling schedules. This work is a continuing effort to validate sensitive biomarkers for endocrine disruption by looking at male vitellogenin expression in relation to fish ecology in Iligan City. Livers of selected sexually mature male and female reef fishes were homogenized in 63mM Tris-HCI pH 6.8 to obtain crude cytoplasmic extracts and subsequently subjected to electrophoration in 12% Tris-glycine pre-cast gels against standard markers and lyophilized carp vitellogenin to show the comparative vitellogenesis in female and male fish livers, with special concern on male vitellogenin expression. Selected fish liver samples were analyzed for expression of putative vitellogenin, distinct high molecular weight (HMW) bands near the 170 - 200kDa range or 97.3 - 110kDa markers. The bands corresponding to three district vitellogenin fractions from male livers of fish samples from Iligan City may imply possible disruption of male endocrine function by expressing apparently identical proteins to female samples. Male reproductive anomalies would have direct or indirect effect to fish ecology in the fishing grounds of the city. These finding confirms the previous observations in M. cephalus and implied wider extent of still unidentified EDCs in the surrounding waters of Iligan, and might as well indicate endocrine disruption in other species and may lead to lower chances of fish recruitment in the bay.